Disappearing Lands: Resource Extraction, Land Use, and Indigenous Land Rights in the Russian Arctic ... - Belolyubskaya, Galina (Graduate Studies, 2025)
This dissertation examines Indigenous land rights in the Republic of Sakha (Yakutia), the largest and one of the most resource-rich regions of Russia. The historical and ongoing expansion of extractive industries continues to profoundly affect the lives of Indigenous communities in the region. One such community is Syuldyukar, a small village located within Sadynsky nasleg in western Sakha—an area that is traditionally the land of the Evenki people. Over time, resource expansion altered Syuldyukar’s social and economic life, leaving lasting marks on land-based traditions. This study draws on a multi-method approach, incorporating legal analysis, archival research, ethnography, and oral history. It begins with an in-depth examination of the concept of osvoenie, which I argue is crucial for understanding Indigenous-state relations in Russia. Osvoenie, often translated from Russian as ‘mastery of land,’ has played a central role in shaping state approaches to land and people in Siberia. Initially tied to the ...